The Rise of New Poets : Thematic Transformation in Arabic Literature from The Umayyad to Abbasid Period - Salma Fitriyani; Nurholis Nurholis; Arfia Diva Alzahra; Mhd. Al. Fadin (Pusat riset dan Inovasi Nasional, 2025)
Arabic literature experienced a significant thematic transformation from the Umayyad to the Abbasid period. In the Umayyad era, poetry was still rooted in classical qasidah, focusing on praise, tribal pride, and romantic ideals. However, the Abbasid era brought a wave of literary renewal, influenced by sociopolitical and cultural shifts. This study explores how these contexts shaped literary themes and styles, using a descriptive qualitative approach through library research and textual analysis. It focuses on works by Al-Farazdaq, Al-Akhtal, Jarir, Abu Nawas, Abu al-Atahiyah, Dibil al-Khuza’i, and Al-Jahiz. The findings reveal that poetry in the Abbasid era became a tool for social criticism, spiritual reflection, and personal expression. Meanwhile, Al-Jahiz significantly advanced Arabic prose, making it more intellectual and educational. This study concludes that Arabic literature evolved not only in form and content, but also in function, reflecting the intellectual and cultural dynamism of Islamic civilization. Keywords: Abbasid; Arabic literature; New Poets; Transformation; Umayyad